Brazilian Nursing Higher Education and sociological's history of identities (Research, Society and Development, 2022)
Objective: to describe how the Nursing higher education in Brazil was processed over time, considering its historical context and the relationship with its identity. Methods: exploratory-descriptive literature review, with a qualitative approach. It is an excerpt from a doctoral thesis. Results: based on the studies listed, a historical reconstruction of the structure of Nursing higher education and its relationship with the construction of the professional identity of undergraduates was established. Conclusions: the organizational historicity narrated infers that by shifting nursing care from the concept of vocation to a concept called scientific, nurses were not able to solve their identity problem. Furthermore, the importance of promoting the review and readjustment of the National Curriculum Guidelines for Nursing Graduation is highlighted, in view of the changes in the labor market and the incisive educational changes determined in the last year for pandemic reasons and which have already been 20 years since these were created.